1990
DOI: 10.1063/1.345367
|View full text |Cite
|
Sign up to set email alerts
|

Lattice and grain boundary self-diffusion in Ni2Si: Comparison with thin-film formation

Abstract: The Ni2Si lattice and grain boundary self-diffusion parameters have been studied using radiotracers 63Ni for Ni diffusion, 68Ge for Si diffusion, conventional sectioning techniques, and bulk specimens. The results obtained show that Ni diffuses faster than Ge(Si) in the lattice (and in the grain boundaries) of Ni2Si, in agreement with the structure of this silicide. The activation energies for Ni lattice and grain boundary diffusion are respectively 2.48 eV (measured between 650 and 910 °C) and 1.71 eV (530–71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 27 publications
1
39
0
1
Order By: Relevance
“…Ciccariello et al for instance showed that the Ni grain boundary and lattice self-diffusion in d-Ni 2 Si play a major role in the growth of the monosilicide. 37 Since Pt resides mainly at the d-Ni 2 Si grain boundaries, Pt can influence the Ni supply to the growing monosilicide and increase the activation energy for Ni diffusion. Moreover, Pt at the Ni 1Àx Pt x Si grain boundaries, or in the Ni 1Àx Pt x Si phase itself, might obstruct the Ni grain boundary diffusion or lattice diffusion respectively, causing an extra increase in activation energy.…”
Section: Discussionmentioning
confidence: 99%
“…Ciccariello et al for instance showed that the Ni grain boundary and lattice self-diffusion in d-Ni 2 Si play a major role in the growth of the monosilicide. 37 Since Pt resides mainly at the d-Ni 2 Si grain boundaries, Pt can influence the Ni supply to the growing monosilicide and increase the activation energy for Ni diffusion. Moreover, Pt at the Ni 1Àx Pt x Si grain boundaries, or in the Ni 1Àx Pt x Si phase itself, might obstruct the Ni grain boundary diffusion or lattice diffusion respectively, causing an extra increase in activation energy.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the global reaction is diffusion-controlled. Nickel is the mobile species in Ni 2 Si and its diffusion via its own sub-lattice by the vacancy mechanism is supposed to control the Ni 2 Si growth (Ciccariello et al, 1990). The activation energies for Ni lattice and grain boundary diffusion have been found to be 2.48 eV and 1.71 eV, respectively.…”
Section: Bulk Ni-sic Diffusion Couplementioning
confidence: 99%
“…More SiC is then decomposed and more Si atoms become available. The supply of Si atoms is then no longer the dominant factor in the formation of Ni 2 Si, because Ni is the dominant diffusing species through Ni 2 Si (Ciccariello et al, 1990). The growth of thin Ni 2 Si films is controlled mainly by the diffusion of Ni along the silicide grain boundaries.…”
Section: Formation Of Ni 2 Si and Its Mechanismsmentioning
confidence: 99%
“…Experimental information is available already for Ni-, [47][48][49][50] Ti-, 51) and Fe- 52) aluminides and a few other compounds, e.g. Ni 2 Si, 53) Ni 2 Si 5 and CoSi 2 .…”
Section: Discussionmentioning
confidence: 99%